Contra Legem Dilemma in Anticipating Legal and Ethical Degradation in Assisted Reproductive Services: A Systematic Review - Darmawansyah, Edwin; Firmansyah, Arif (Riviera Publishing, 2026)
The rapid advancement of assisted reproductive technologies (ART) has outpaced legal and ethical frameworks across many jurisdictions, creating regulatory gray zones where practices operate without explicit legal authorization or in potential conflict with positive law (contra legem). This misalignment generates legal uncertainty, ethical dilemmas, and risks of normative degradation. This systematic review aims to synthesize the literature on contra legem practices in ART, examine the legal and ethical dilemmas they generate, and identify strategies to anticipate and prevent normative degradation. A systematic review following PRISMA guidelines was conducted using PubMed and Scopus for studies published between January 2015 and December 2025. The Population-Exposure-Outcome (PEO) framework guided the search strategy. Studies addressing ART practices from legal, ethical, or health policy perspectives and examining contra legem situations were included. Data were synthesized using qualitative, narrative thematic analysis. Twelve studies met the inclusion criteria, examining surrogacy, gamete donation, postmortem embryo transfer, and cross-border reproductive care across multiple jurisdictions. The findings reveal substantial regulatory fragmentation, with contra legem practices arising from regulatory gaps, legal uncertainty, and the absence of international harmonization. Key ethical concerns include the commercialization of reproduction, the exploitation of vulnerable women, the instrumentalization of embryos, and the weakening of bioethical principles. Cross-border reproductive care emerges as a significant driver of legal evasion. Contra legem practices in ART reflect structural misalignments between technological innovation and governance frameworks. Strengthening ART governance requires comprehensive, technology-sensitive legislation, specialized oversight mechanisms, and international regulatory coordination to ensure legally secure and ethically robust reproductive health services.